„Dimineaţa poeticească” a lui Ioan Cantacuzino (1757–1828) - Eugen Simion (Revista de Istorie și Teorie Literară)
Ioan Cantacuzino’s ‘poetical morning’ attests a precursor, we may say, of Arghezi, an authentic lyrical spirit who is more complex, cultivated and open towards the West than that of other authors of rhymes of his age, as is revealed by such writings as those entitled ‘Cântec beţivesc’ (= A Drunkard’s Song) and ‘Răsuflare’ (= Breath), but more especially by his translations of the ‘Song of Songs’ and, due to a mediated French-channeled assistance, his translations of pre-Romantic English poetry.